Two of the Trinidad and Tobago Marine Police Launch 'Seahawk'. (1960)
This is an image of two of the crew of the Trinidad and Tobago Marine Police Launch 'Seahawk'.
Good Condition
This image is not digitized.
This image is available on the Special Collections Floor.
Keywords: Trinidad. -- Photographs. -- Jamaica; Photograph